Analisis Kesalahan Berbahasa dalam Pelajaran Insya’ Siswa Kelas IV KMI Pondok Modern Ar-Risalah Slahung Ponorogo - Nurcahyaningtias, Novia Dwi (Mahira: Journal of Arabic Studies, 2021)
One obstacle in communication process is lack of language skills. Lack of language skills is partly caused by language errors. In the use of language specifically, sometimes language errors are deliberately made or realized by speakers to achieve certain effects such as being funny, attracting attention and encouraging more intense thinking. Although there is not much attention to language errors, thoughts about the relationship between language errors and the process of learning language in a relatively short time have developed a lot. In the world of language teaching, attention to language errors has only developed over a relatively recent period of time. The development of thinking regarding the relationship between language errors and the language learning process is in line with the results of the analysis which are expected to assist teachers in determining the order of teaching materials, deciding on the emphasis, explanation and practice needed, providing remedial and exercises, and selecting items. second language items for the purposes of the learner proficiency test. This research on the analysis of language errors in the fourth grade students of KMI Ar-Risalah Islamic Boarding School Slahung Ponorogo lessons uses a qualitative approach. This research is categorized as a descriptive study because the researcher describes the data on language errors contained in the students' essays. The data in this study are in the form of language errors contained in student essays. Sources of data in this study is student essays. Data collection uses the documentation method. The results showed that the error in the use of vocabulary recorded the number of errors as many as 15 errors (18.75%). The frequency of errors in the use of phrases, namely 25 errors (31.25%) and errors in the use of pronouns and errors in the use of gender, respectively recorded the number of errors of 15 errors (18.75%) and 25 errors (31.25%).